Collective flux pinning in hexatic vortex fluid in a-MoGe thin film. (13th November 2019) - Dutta, Surajit; Roy, Indranil; Basistha, Somak; Mandal, Soumyajit; Jesudasan, John; Bagwe, Vivas; Raychaudhuri, Pratap
Abstract: We investigate the magnetic field variation of the thermally activated flux flow resistivity, ρ TAFF and flux flow critical current density, J c, in a weakly pinned thin film of the amorphous superconductor a -MoGe, where vortices are in a fluid state over a large range of magnetic fields. We show that both quantities can be understood within the framework of collective pinning theory. In particular, our results demonstrate that a 'peak effect' can arise at the order–disorder transition of the vortex lattice even when both the ordered and disordered states are vortex fluids, such as the boundary between a hexatic vortex fluid and an isotropic vortex liquid.